IMPACT OF THE QUALITY OF INTEGRATED ADMINISTRATION SERVICES (PATENTS) ON IDENTITY TREATMENT SERVICES FOR DOUBLE CITIZENSHIP IN THE NORTHERN KALIMANTAN PROVINCE - Muhamad Yusuf (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Bureaucratic reform is the government's effort to improve public services that have not met people's expectations. This is due to ignorance of public services, and unresponsive service delivery. This study aims to find out how the integrated administrative service innovation (PATEN) influences the handling of dual citizenship identities in Nunukan Regency, North Kalimantan Province. This study used a quantitative approach with a simple random sampling measurement method in Nunukan Regency. The results of the study show that there is a positive and significant relationship between the service quality variable and the satisfaction variable in handling dual citizenship identity in Nunukan Regency, North Kalimantan Province. Obstacles and obstacles faced by the Nunukan Regency government in handling dual citizenship identity, namely the low ability of the government seen from the level of education and suitability in supporting service tasks, limited service facilities and facilities in supporting service tasks, resulting in limitations in area coverage, borders that are difficult to pass because territorial waters, low community participation in ownership of identity cards (KTP).